Technological revolutions and speculative finance: Evidence from the British Bicycle Mania - William Quinn (Queen's University Centre for Economic History (QUCEH), 2016)
Technological revolutions are often accompanied by substantial stock price reversals, but previous literature has produced competing explanations for why this is the case. This paper brings new evidence to this debate using data from the innovation-driven British Bicycle Mania of 1895-1900, in which cycle share prices rose by over 200 per cent before collapsing by more than 75 per cent. These price patterns are not fully explained by fundamentals or by changes in the nature of risk associated with cycle shares. Instead, the evidence from the Bicycle Mania supports the hypothesis of Perez (2009), who argues that new technology, high short-term profits, and loose monetary conditions increase the level of speculative investment, "decoupling" share prices from fundamentals.
Keywords: G19; N23; O39; 330; technology; innovation; historical stock markets; asset price reversals